The Structure of a Rawlsian Theory of Just Work - Lindblom, Lars (2011)
This article outlines the structure of a Rawlsian theory of justice in the employment relationship. A focus on this theory is motivated by the role it plays in debates in business ethics. The Rawlsian theory answers three central questions about justice and the workplace. What is the relationship between social justice and justice at work? How should we conceive of the problem of justice in the economic sphere? And, what is justice in the workplace? To see fully what demands justice makes on the workplace, we should first spell out the implications that domestic justice has for working conditions. When this is done, we can develop a conception of workplace justice and investigate what content such local justice should have. John Rawls’s political liberalism was constructed for the specific problem of a just basic structure; in order to apply it to another problem the key theoretical concepts must be revised. Reasons for a specific construction of a local original position are given and arguments are presented in support of a principle of local justice, which takes the form of a choice egalitarian local difference principle.
Keywords: workplace justice; Work; Responsibility; Reciprocity; local justice; justice as fairness; employment contracts; Desert; choice egalitarianism